The Influence of Frequency, Volume, and Viscosity on the Ultrasonic Atomization Threshold of Sessile Droplets - Gaete-Garreton, L; Vargas-Hernandez, y; Meneses-Díaz, J; Cancino-Jaque, E (Acoustical Society of America, 2024)
In this research, we present a study on the atomization threshold ( A T h ) of sessile droplets, analyzing its relationship with the excitation frequency f exc ( 55 - 48 kHz ), droplet volume V drop ( 1 - 100 μ l ), and droplet viscosity μ ( 1 - 6 mPa ⋅ s ). The investigation focused on the atomization thresholds using ultrasonic excitation of distilled water droplets and water- polyethylene glycol (PEG)-8000 mixtures deposited on vibrating surfaces. The obtained results are compared with previously reported theoretical models. A modification to the model proposed by Alzuaga et al. [Alzuaga, Manceau, and Bastien, J. Sound Vib. 282(1-2), 151-162 (2005)] is suggested to determine the atomization thresholds of sessile droplets, incorporating the atomization droplet size equation proposed by Rajan and Pandit and an empirical constant α to account for the effect of droplet volume in this process. The results show that the relationship between the atomization threshold and viscosity does not fit well with the prediction of Eisenmenger [Acta Acust united Acust. 9(4), 327-340 (1959)] and Pohlman and Stamm [Untersuchung Zum Mechanismus Der Ultraschallvernebelung an Flüssigkeitsoberflächen im Hinblick Auf Technische Anwendungen (Investigation on the Mechanism of Ultrasonic Nebulization on Liquid Surfaces Considering Technical Applications) (VS Verlag für Sozialwissenschaften, Wiesbaden, Germany, 1965)] and Pohlman et al. [Pohlman, Heisler, and Cichos, Ultrasonicc 12(1), 11-15 (1974)] ( A T h ∝ μ ). However, the data tendency aligns with the model proposed by Alzuaga ( A T h ∝ μ 1 / 2 ). The results obtained in this study provide a deeper understanding of the atomization thresholds of sessile droplets through ultrasonic excitation. © 2024 Acoustical Society of America.